2019
DOI: 10.32098/mltj.01.2016.14
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of hamstring injury in professional soccer players by isokinetic measurements

Abstract: Objectives: previous studies investigating the ability of isokinetic strength ratios to predict hamstring injuries in soccer players have reported conflicting results. Hypothesis: to determine if isokinetic ratios are able to predict hamstring injury occurring during the season in professional soccer players. Study Design: case-control study; Level of evidence: 3. Methods: from 2001 to 2011, 350 isokinetic tests were performed in 136 professional soccer players at the beginning of the soccer season. Fifty-seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 28 publications
4
54
1
5
Order By: Relevance
“…Isokinetic testing in soccer players is a frequent routine procedure for fitness evaluation, but it is not always predictive of soccer functional performance (Requena et al, 2009). However, isokinetic testing is considered a valid and reliable tool for assessing lower body muscle performance and asymmetries that could lead to musculoskeletal injuries (Dauty et al, 2016). In addition to the hip adductor muscle group, professional soccer players exhibit the highest injury rate on quadriceps and hamstrings muscle groups (Hagglund et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isokinetic testing in soccer players is a frequent routine procedure for fitness evaluation, but it is not always predictive of soccer functional performance (Requena et al, 2009). However, isokinetic testing is considered a valid and reliable tool for assessing lower body muscle performance and asymmetries that could lead to musculoskeletal injuries (Dauty et al, 2016). In addition to the hip adductor muscle group, professional soccer players exhibit the highest injury rate on quadriceps and hamstrings muscle groups (Hagglund et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Video analysis has demonstrated that soccer players are often involved in high intensity activities that require significant levels of lower body strength (Schuth et al, 2016). The frequent unilateral use of the limbs in soccer (Reilly et al, 2000) may result in strength deficits between the two limbs, and thus increase the rate of musculoskeletal injuries in elite soccer players (Croisier et al, 2008;Dauty et al, 2016). Furthermore, Ezechieli et al (2013) demonstrated Journal of Human Kinetics -volume 70/2019 http://www.johk.pl that soccer specific training did not lead to balanced trunk musculature and core stability, and thus increased the chance of injury, muscle imbalance, and triggered pain syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…This appears to be supported by the fact that the cut-off scores defined by some prospective studies (mainly those related to strength measurements) have not been later ratified by others using similar designs and assessment methodologies but with different samples of soccer players [3, 9, 12-14, 20, 25, 37, 38]. For example, while Croisier et al [12] and Dauty et al [14] found that professional soccer players with reciprocal (functional) hamstring-to-quadriceps strength ratios (H/Q) lower than 0.8 were at higher risk of sustaining an HSI, van Dyk et al [38] did not identify this strength ratio measure as a risk factor for HSI. The second issue with the current body of the literature is that most of the available studies have identified potential risk factors for HSI according to the presence of statistically significant relationships with HSI (e. g., based on odds ratios, certain values of the p statistic [mainly p < 0.05]).…”
Section: Introductionmentioning
confidence: 99%
“…Introdução O futebol é considerado uma modalidade esportiva que solicita dos jogadores, além de, condições técnicas e táticas, diferentes formas de expressão da aptidão física, sobretudo a força muscular 1 . No futebol, a força tem um papel decisivo em diferentes ações realizadas durante uma partida, tais como: corridas (sprint), saltos verticais, chutes, passes, desarmes e mudanças de direção, e estas ações dependem, da contribuição eficiente e sinérgica do sistema neuromuscular para produção de força e potência na execução de cada tarefa 2,3 A avaliação da força muscular realizada em dinamômetro isocinético vem sendo utilizada como marcador da função e desempenho de diferentes grupos musculares 4 . Os estudos realizados por Fonseca et al 5 , Zabka, Valente e Pacheco 6 , analisaram a partir das variáveis da função muscular o desempenho em força de jogadores de futebol.…”
Section: Revisões De Literaturaunclassified